Effect of player position on movement behaviour, physical and physiological performances during an 11-a-side football game - Gonçalves, B. V.; Figueira, B. E.; Maçãs, V.; Sampaio, J. (Journal of Sports Sciences, 2014)
The aim of this study was to identify differences in time-motion, modified training impulse, body load and movement behaviour between defenders, midfielders and forwards, during an 11-a-side simulated football game. Twenty elite youth male footballers from the same squad participated in this study (age: 18.1 ± 0.7 years old, body mass: 70.5 ± 4.3 kg, height: 1.8 ± 0.3 m and playing experience: 9.4 ± 1.3 years). All data were collected using GPS units (SPI-Pro, GPSports, Canberra, Australia). The movement behaviour was measured with kinematic data, used to calculate position-specific centroids (defenders, midfielders and forwards), and processed with non-linear statistical procedures (approximate entropy normalised and relative phase). There were significant effects and interactions in all variables across the players` positions. The results showed that displacements of all players (defenders, midfielders and forwards) were nearer and more coordinated with their own position-specific centroids than with the other centroids. However, this coupling effect was stronger in midfield players and weaker in forwards. All players` dynamical positioning showed more irregularity when related to the forwards` centroid, as a consequence of their need to be less predictable when playing. The time-motion and physiological variables showed lower activity in forward players. Adding together, the results may contribute to a better understanding of players` specific performances and football complexity.